An examination of works for band: Southern folk rhapsody, arranged by Michael Sweeney, On a hymnsong of Philip Bliss, arranged by David Holsinger, Music from wicked, arranged by Michael Sweeney, Whispers of the wind, by David Shaffer - Eastvold, Jared (Kansas State University, 2007)
The following report is research and analysis from the comprehensive examination question based on the Graduate Conducting Recital of Jared Eastvold. The recital was performed by the Leyton High School Band, on on May 8, at 7:00 p.m., in Dalton, Nebraska. The repertoire included Southern Folk Rhapsody, arranged by Michael Sweeney; On a Hymnsong of Philip Bliss, arranged by David Holsinger; Music from Wicked, arranged by Michael Sweeney; and Whispers of the Wind, by David Shaffer. This document contains analysis, both theoretical and historical, and outlines the procedures of planning and performing the graduate conducting recital. This report also includes a detailed analysis of the recital music, using both the Blocher/Miles and the Tracz formats. A philosophy of music education is presented as the foundation to planning rehearsals and selecting the music for the recital. An overview of the music program at Leyton is given to provide background to the performance organization. Comprehensive rehearsal plans for the works are also given.
Keywords: Band; Literature; Music (0413)